An ELISA method for the detection and quantification of human heparanase - Shafat, Itay (2006)
Heparanase is a mammalian endo-β-D-glucuronidase that cleaves heparan sulfate (HS) side chains at a limited number of sites. Heparanase enzymatic activity is thought to participate in degradation and remodeling of the extracellular matrix (ECM) and to facilitate cell invasion associated with tumor metastasis, angiogenesis and inflammation. Traditionally, heparanase activity was well correlated with the metastatic potential of a large number of tumor-derived cell types. More recently, heparanase up regulation was detected in an increasing number of primary human tumors, correlating, in some cases, with poor postoperative survival and increased tumor vascularity. The present study was undertaken to develop a highly sensitive ELISA assay suitable for the determination and quantification of human heparanase in tissue extracts and body fluids. The assay preferentially detects the 8+50 kDa active heparanase heterodimer vs. the latent 65 kDa pro-enzyme and correlates with immunoblot analysis of heparanase containing samples. It detects heparanase at concentrations as low as 200 pg/ml, and is suitable for quantification of heparanase in tissue extracts and urine.